2021
DOI: 10.1186/s12958-021-00857-3
|View full text |Cite
|
Sign up to set email alerts
|

CircCRIM1 promotes ovarian cancer progression by working as ceRNAs of CRIM1 and targeting miR-383-5p/ZEB2 axis

Abstract: Background Ovarian cancer is the leading cause of death in patients with gynecologic cancer, and circular RNAs (circRNAs) are involved in cancer progression. However, there are limited studies on the roles of circRNAs in ovarian cancer. Methods We designed divergent and convergent primers, used sanger sequencing and RNase R digestion to verify the source of circCRIM1. We detected the expression of circCRIM1 and its parental gene cysteine rich trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…We further demonstrated that circ_0000098 regulated MCUR1 expression by competitive bonding with miR-383. According to previous reports, miR-383 is dysregulated in several cancers and controls their growth [ 28 , 29 ]. Long non-coding RNA CASC9-1 promotes cervical cancer progression by targeting miR-383 to upregulate MAPKAP1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further demonstrated that circ_0000098 regulated MCUR1 expression by competitive bonding with miR-383. According to previous reports, miR-383 is dysregulated in several cancers and controls their growth [ 28 , 29 ]. Long non-coding RNA CASC9-1 promotes cervical cancer progression by targeting miR-383 to upregulate MAPKAP1 [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Long non-coding RNA CASC9-1 promotes cervical cancer progression by targeting miR-383 to upregulate MAPKAP1 [ 28 ]. CircCRIM1 also promotes the tumorigenesis of ovarian cancer by targeting the miR-383/ZEB2 axis [ 29 ]. In our study, in vitro experiments supported that circ_0000098 increases HCC development through the miR-383/MCUR1 axis, however, the detailed impact of this signaling on HCC remains to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…circCRIM1 was implicated in promoting ovarian cancer progression by acting as a competitive endogenous RNA (ceRNA) for the host gene CRIM1 and targeting the miR-383-5p/ZEB2 axis [ 65 ]. CRIM1 encodes a transmembrane protein containing six cysteine-rich repeat domains and an insulin-like growth-factor-binding domain.…”
Section: Discussionmentioning
confidence: 99%
“…CircCRIM1 harbors an ORF with 188 amino acids spanning the splice junction. Overexpression of this protein induced cell viability, migration and invasion, and inhibited apoptosis in EOC, suggesting a tumor-promoting activity of the circCRIM1-encoded protein [ 171 ]. However, whether circCRIM1 is endogenously translated into the protein remains to be confirmed.…”
Section: Circrnas As Potential Therapeutic Targetsmentioning
confidence: 99%